Hand Grip Test in Post-COVID-19 Patients: Late Impacts of the Infection - Pereira Junqueira de Oliveira, Maria Alice; Sampaio Monteiro, Josué Natã; Montessi Amorim, Giovanna; Sant’Ana Costa, Bruno; Mendonça Pereira Amaral, Juliana; de Oliveira Sousa Corrêa, Vivian (Fisioterapia & Saúde Funcional, 2025)
This study aims to evaluate hand grip strength in individuals post-SARS-CoV-2 infection, comparing results with normative values from the literature. Twenty-three Brazilian participants aged 18-59 who had COVID-19 underwent hand grip testing using a dynamometer. Their results were compared to expected values based on gender and age. For the female participants in this study, the mean grip strength was 21.45 ± 5.94 kgf for the dominant hand and 21.06 ± 5.80 kgf for the non-dominant hand. In the male group, the mean grip strength was 23.65 ± 6.02 kgf for the dominant hand and 19.57 ± 2.53 kgf for the non-dominant hand. The comparison indicated that, for both genders, the average grip strength recorded in this study was significantly lower than the expected values for the population. SARS-CoV-2 infection leads to compromised muscle function. The hand grip test is a low-cost, easy-to-use tool for assessing and managing patients with various conditions.